1994
DOI: 10.1046/j.1471-4159.1994.63051962.x
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone Increases Adrenalectomy‐Depressed Na+,K+‐ATPase mRNA and Ouabain Binding in Spinal Cord Ventral Horn

Abstract: The Na+,K'-ATPase plays a key role in the regulation of ion fluxes and membrane repolarization in the CNS . We have studied glucocorticoid effects on biosynthesis of the Na+,K+-ATPase and on ouabain binding in the ventral horn of the spinal cord using intact rats, adrenalectomized (ADX) rats, and ADX rats receiving dexamethasone (ADX + DEX) during 4 days . Cryostat sections from spinal cords were incubated with a 35Soligonucleotide coding for the a3-subunit or a 3H-cDNA coding for the 01-subunit of the Na+,K+-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Hormones are major regulators of Na,K-ATPase expression. Mineralocorticoids (Verrey et al, 1987 , 1988 , 1989 ; Ikeda et al, 1991 ; Oguchi et al, 1993 ; Farman et al, 1994 ; Muto et al, 1996 ; Tsuchiya et al, 1996 ; Grillo et al, 1997 ; Seok et al, 1999 ; Olivera et al, 2000 ; Blot-Chabaud et al, 2001 ; Phakdeekitcharoen et al, 2011 ), glucocorticoids (Orlowski and Lingrel, 1990 ; Bhutada et al, 1991 ; Celsi et al, 1991 ; González et al, 1994 , 1996 ; Muto et al, 1996 ; Barquin et al, 1997 ; Ingbar et al, 1997 ; Chalaka et al, 1999 ; Dagenais et al, 2001 ; Hao et al, 2003a , b ), thyroid hormone (McDonough et al, 1988 ; Gick and Ismail-Beigi, 1990 ; Orlowski and Lingrel, 1990 ; Melikian and Ismail-Beigi, 1991 ; Hensley et al, 1992 ; Kamitani et al, 1992 ; Azuma et al, 1993 ; Giannella et al, 1993 ; Ohara et al, 1993 ; Huang et al, 1994 ; Lin and Tang, 1997 ; Bajpai and Chaudhury, 1999 ; Shao et al, 2000 ; Phakdeekitcharoen et al, 2007 ), insulin (Russo and Sweadner, 1993 ; Tirupattur et al, 1993 ; Sweeney and Klip, 1998 ), progesterone (Cochrane et al, 2012 ; Deng et al, 2013 ), androgen (Blok et al, 1999 ), and vitamin D3 (Billecocq et al, 1997 ) have been reported to activate or repress Na,K-ATPase transcription. These hormones bind to and activate their receptors, which belong to the family of nuclear receptors with C4 zinc-fingers that then translocate into the nucleus to bind to the promoter regions of the target genes to regulate gene expression.…”
Section: Transcriptional Regulation Of Nak-atpase By Hormones and Numentioning
confidence: 99%
See 1 more Smart Citation
“…Hormones are major regulators of Na,K-ATPase expression. Mineralocorticoids (Verrey et al, 1987 , 1988 , 1989 ; Ikeda et al, 1991 ; Oguchi et al, 1993 ; Farman et al, 1994 ; Muto et al, 1996 ; Tsuchiya et al, 1996 ; Grillo et al, 1997 ; Seok et al, 1999 ; Olivera et al, 2000 ; Blot-Chabaud et al, 2001 ; Phakdeekitcharoen et al, 2011 ), glucocorticoids (Orlowski and Lingrel, 1990 ; Bhutada et al, 1991 ; Celsi et al, 1991 ; González et al, 1994 , 1996 ; Muto et al, 1996 ; Barquin et al, 1997 ; Ingbar et al, 1997 ; Chalaka et al, 1999 ; Dagenais et al, 2001 ; Hao et al, 2003a , b ), thyroid hormone (McDonough et al, 1988 ; Gick and Ismail-Beigi, 1990 ; Orlowski and Lingrel, 1990 ; Melikian and Ismail-Beigi, 1991 ; Hensley et al, 1992 ; Kamitani et al, 1992 ; Azuma et al, 1993 ; Giannella et al, 1993 ; Ohara et al, 1993 ; Huang et al, 1994 ; Lin and Tang, 1997 ; Bajpai and Chaudhury, 1999 ; Shao et al, 2000 ; Phakdeekitcharoen et al, 2007 ), insulin (Russo and Sweadner, 1993 ; Tirupattur et al, 1993 ; Sweeney and Klip, 1998 ), progesterone (Cochrane et al, 2012 ; Deng et al, 2013 ), androgen (Blok et al, 1999 ), and vitamin D3 (Billecocq et al, 1997 ) have been reported to activate or repress Na,K-ATPase transcription. These hormones bind to and activate their receptors, which belong to the family of nuclear receptors with C4 zinc-fingers that then translocate into the nucleus to bind to the promoter regions of the target genes to regulate gene expression.…”
Section: Transcriptional Regulation Of Nak-atpase By Hormones and Numentioning
confidence: 99%
“…Glucocorticoids regulate the transcription of Na,K-ATPase in a variety of tissues including lung, kidney, liver, heart, spinal cord, cardiac muscle and smooth muscle (Orlowski and Lingrel, 1990 ; Bhutada et al, 1991 ; Celsi et al, 1991 ; Wang and Celsi, 1993 ; González et al, 1994 , 1996 ; Wang et al, 1994 ; Muto et al, 1996 ; Barquin et al, 1997 ; Ingbar et al, 1997 ; Chalaka et al, 1999 ; Dagenais et al, 2001 ; Hao et al, 2003b ). This regulation is specific to the cell type and the developmental stage.…”
Section: Transcriptional Regulation Of Nak-atpase By Hormones and Numentioning
confidence: 99%